2007
DOI: 10.1021/bi602347g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Heparin and Glucan Sulfates Binding to P-Selectin and Its Impact on the General Understanding of Selectin Inhibition

Abstract: P-Selectin, expressed on activated endothelial cells and platelets, is a high kinetic adhesion receptor involved in leukocyte rolling of the inflammatory response, or in tumor cell binding in the course of metastasis. Thus, P-selectin inhibition is a promising therapeutic target. The anti-inflammatory and anti-metastatic activities of heparin have partly been related to the inhibition of P-selectin binding. Here we apply a quartz crystal microbalance (QCM) biosensor to determine the kinetic constants of hepari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 46 publications
1
24
0
2
Order By: Relevance
“…34 Because of its net negative charge, heparin, like other glycosaminoglycans, is able to bind and concentrate growth factors and chemokines on the cell surface. 35 It has also been exploited to bind and purify numerous protein components of platelet ␣-granules, including von Willebrand factor, 36 fibronectin, 37 Pselectin, 38 thrombospondin, 39 vitronectin, 40 and PF4. 41 Interestingly, and relevant to this discussion, heparin has been shown to bind a number of transmembrane glycoproteins, including the Washed platelets were stirred at 1000 rpm at 37°C alone or in the presence of heparin with or without 6.67 g/mL eptifibatide, lysed, and subjected to immunoblot analysis as described in the legend to Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…34 Because of its net negative charge, heparin, like other glycosaminoglycans, is able to bind and concentrate growth factors and chemokines on the cell surface. 35 It has also been exploited to bind and purify numerous protein components of platelet ␣-granules, including von Willebrand factor, 36 fibronectin, 37 Pselectin, 38 thrombospondin, 39 vitronectin, 40 and PF4. 41 Interestingly, and relevant to this discussion, heparin has been shown to bind a number of transmembrane glycoproteins, including the Washed platelets were stirred at 1000 rpm at 37°C alone or in the presence of heparin with or without 6.67 g/mL eptifibatide, lysed, and subjected to immunoblot analysis as described in the legend to Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…GlcN6S in heparin is critical for interactions with P-and L-selectin [37]. P-selectin binds to heparin with a slow off-rate and a K d of 115 nM according to surface plasmon resonance [38], and 1210 to 580 nM according to quartz crystal microbalance [39].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Bachelet et al (2009) showed that fucoidan prevented P-selectin binding to sLeX. Simonis et al (2007) demonstrated the specificity of the interaction between P-selectin and fucoidan. Rinetic studies have shown that a much slower dissociation of the fucoidan from the receptor than the physiological ligands is key for inhibitory capacity.…”
Section: L-and P-selectin Cd11b/cd18mentioning
confidence: 95%